2006
DOI: 10.1590/s1519-69842006000500008
|View full text |Cite
|
Sign up to set email alerts
|

Protected cerrado fragments grow up and lose even metapopulational birds in central São Paulo, Brazil

Abstract: ABSTRACTmoderately dense woodland (cerradão) grew in two isolated patches of bushy savanna (cerrado) in central são Paulo over 23 years of bird censuses. various uncommon birds were lost and some forest species were permanently gained. Fall and winter fruits attract long and short-distance migrants. woodpeckers and some birds that nest in their holes seem to disappear during tree growth. some birds in weedy areas nearby disappeared when the pastures replaced these areas, however sugar cane reduced the numbers … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 6 publications
1
6
0
1
Order By: Relevance
“…Although the sampling efforts differed considerably in these studies and comparing them seems inappropriate, these patterns were nonetheless corroborated ( Table 2). Similarity indexes were highest between the municipalities of Bauru and Corumbataí, São Paulo (Willis, 2006), and lowest between Amazonia-influenced Serra do Roncador, Mato Grosso (Fry, 1970) and Agudos, São Paulo (Almeida, 1979). There were no species shared among all of the analyzed inventories, but some tended to be present in most locations, such as the Flavescent Warbler Basileuterus flaveolus, a very common species of both cerradões and semi-deciduous forests from the Cerrado domain (Sick, 1997).…”
Section: Location (Reference) Species Richness Habitat Remnant Size Mmentioning
confidence: 99%
See 2 more Smart Citations
“…Although the sampling efforts differed considerably in these studies and comparing them seems inappropriate, these patterns were nonetheless corroborated ( Table 2). Similarity indexes were highest between the municipalities of Bauru and Corumbataí, São Paulo (Willis, 2006), and lowest between Amazonia-influenced Serra do Roncador, Mato Grosso (Fry, 1970) and Agudos, São Paulo (Almeida, 1979). There were no species shared among all of the analyzed inventories, but some tended to be present in most locations, such as the Flavescent Warbler Basileuterus flaveolus, a very common species of both cerradões and semi-deciduous forests from the Cerrado domain (Sick, 1997).…”
Section: Location (Reference) Species Richness Habitat Remnant Size Mmentioning
confidence: 99%
“…These authors only mentioned those species with more than five captures. Willis (2006) recorded 56 species in São Paulo when border and flying over species are excluded. Manica et al (2010) found 29 species in a cerradão remnant in São Paulo, but this cerradão was the least visited habitat by the authors.…”
Section: Bauru Cerradãomentioning
confidence: 99%
See 1 more Smart Citation
“…Species composition was compared to other areas of Cerrado within Sã o Paulo, namely: Botanical Garden/UNESP Reserve in Bauru (Cavarzere et al 2011), Canchim Farm in São Carlos (Manica et al 2010), UNESP Reserve in Corumbataí (Willis 2006), Itirapina Ecological Station (Willis 2004, Motta-Jú nior et al 2008, Fieker et al 2013, Itirapina Experimental Station , Jataí Ecological Station (Dias 2000), Cerrado Pé-de-Gigante/Vassununga State Park (Willis & Oniki 2003, Develey et al 2005, and UFSCar, campus Sã o Carlos (Motta-Jú nior 1990) ( Figure 1). Similarities (Jaccard's index) between areas were evaluated through the UPGMA clustering analysis with Euclidean distance matrix, using the R stats package (R Development Core Team 2008).…”
Section: Bird Censusmentioning
confidence: 99%
“…Um dos pressupostos deste modelo é que as extinções locais podem ser balanceadas por recolonização proveniente de populações de fragmentos florestais vizinhos (Metzger, 1999;Willis, 2006;Hayden e Pianka, 1999). Neste ponto uma pergunta é pertinente: Quais os fatores que levam uma metapopulação a se extinguir?…”
Section: Remanescentes De Floresta Atlântica E Modelos Ecológicosunclassified